Perspektif Keluarga tentang Kebijakan Pendidikan Anak - Seka Andrean; Wildan Nuril Ahmad Fauzi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2020)
The first education a child obtains is through the family. The purpose of this study is to find out about how children's education policy is in the perspective of the family environment. The method used is library research. The results showed that the family is not just a gathering place for fathers, mothers and children. But it is in the family that the individual develops and that is where the beginning of the socialization process is formed and through interaction with him he acquires his knowledge, skills, interests, values, emotions, and attitudes in life and thus he obtains tranquillity and tranquillity. Factors that affect the way parents educate, relationships between family members, the atmosphere of the house, the state of the family economy, the understanding of parents, and the background of family culture